The Impact of Brand Image, Brand Awareness, Service Quality, and Price on Customer Satisfaction with Go-Ride Services: A Case Study of Gojek in Management Students Class of 2019, Faculty of Economics & Business Riau Kepulauan University Batam - Ramli, Rimayang Anggun; Hisyam, Magneta; Sinamo, Juan Andreas (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research was conducted to determine the effect of brand image, brand awareness, service quality, and price on customer satisfaction, both separately (partially) and together (simultaneously). In this study the authors used a sample of 63 respondents, data collection techniques were carried out by distributing questionnaires. The measurement scale used is theLikert scale and for testing it uses the Statistical Product and Service Solution (SPSS) version 22 program. From the results of this study the authors conclude that partially calculating Brand Image (X1) has a positive but not significant effect on customer satisfaction, with a t- value of 1,675 with a significance of 0,099. Brand Awareness (X2) has a positive but not significant effect on customer satisfaction, with a t value of 1,765 with a significant level of 0,083. Service Quality (X3) has a negative and insignificant effect on customer satisfaction, with t count 0,068 with a significant level of 0,639. Price (X4) has a negative and insignificant effect on customer satisfaction, with t count -0,163 with a significant level of 0,211. Judging from the simultaneous test or jointly knowing the effect of Brand Image (X1), Brand Awareness (X2), Quality of Service (X3), and Price (X4) simultaneously has a positive and significant effect on the variable Customer Satisfaction (Y) with calculated f value of 5,052 with a significant level of 0.001.